Suara dari Alam Kubur: Mati Jadi Hantu dan Kekerasan terhadap Perempuan di Kalimantan Selatan - Mursalin, Mursalin (Pusat Studi Gender dan Anak Universitas Islam Negeri Antasari Banjarmasin, 2024)
The incidence of violence against women in South Kalimantan has significantly increased, from 531 cases in 2023 to 655 cases in 2024. Amid these rising numbers, a cultural narrative surrounding urang mati jadi hantu (the dead becoming ghosts) often emerges in connection with the deaths of women victims of violence. This study explores the relationship between supernatural beliefs and violence against women in Banjar society, focusing on the use of mystical practices by victims as a form of self-defense, analyzed through the lens of the Learned Helplessness theory. Using Spradley’s ethnographic method, the research was conducted across six regions in South Kalimantan, involving informants familiar with the phenomenon. The findings reveal four patterns in the use of mystical practices: to protect against social stigma, respond to physical violence, manage verbal abuse, and prevent marital infidelity. The analysis, framed by the Learned Helplessness theory, suggests that reliance on mystical practices reflects victims' powerlessness and the inadequacies of formal protection systems. Rather than alleviating their situation, these practices exacerbate it by perpetuating social stigma, even after the victim’s death. The study concludes that more effective protection systems are needed, ones that balance cultural sensitivities with concrete legal and psychosocial interventions in addressing violence against women. Keywords: Banjar; Ghost; Violence; Women